ANALISIS EFISIENSI MODAL KERJA DAN PROFITABILITAS PADA CV ASRI TATATIRTA DI SAMARINDA KALIMANTAN TIMUR - Nanik Iswahyuni; Siti Masyithoh; Musviyanti Musviyanti (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Nanik Iswahyuni, The Analysis of Network Capital and Pofitability In CV Asri Tatatirta Samarida East Kalimantan, under the guidance of Ms Siti Masyithoh ad Ms.Musviyanti. The research is a quantitive research. The purpose of this research was to know the efficiency of Network Capital and Provitability reviewed by the ratio of  activity ad provitability in CV Asri Tatatirta  period 2014 to 2017. The subject of this research is CV Asri Tatatirta . CV Asri Tatatirta is a corporate works on water reservoirs, purify cation, distribution, design, mechanical and electrical, and waste water recycle became clean water. The object of this research is financial statement, period 2014 to 2017, consist of balance sheet items of trial balance and income statement.            The data collection method used in this research is documentation. The data analysis method used in this research is financial ratio analysis. The data analysis method used in the research is quantitive descriptive.            The result of this research is CV Asri Tatatiirta could manage the network capital efficiently based on the total asset turnover, receivable turnover, and network capital turnover. And also the highest profitability level is on 2014.